TEKNIK SINEMATOGRAFI DALAM FILM BARA (THE FLAME) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This research focuses on cinematography techniques through visual disclosure. This study aims to find out the narrative camera technique used in the documentary film "Bara (The Flame)", knowing the message of cinematograph techniques in the documentary film "Bara (The Flame)" in the study of narrative camera techniques. The narrative camera itself is used as a character in a camera setup by a filmmaker and is also used to build messages through visuals built into the film. This type of research is curative research with qualitative descriptive methods, the data used in this study are visual data obtained from a cinematographic approach. Research data was obtained from the visuals in the film Bara (The Flame). Additional data was obtained from interviews with filmmakers and producers from Arfan Sabran and Ishak Iskandar. Data is obtained from documentation techniques by watching films repeatedly so as to get the data needed. The data obtained in this film is in the form of shot pieces containing messages (non-verbal) in the form of behavior/morals of Mr. Iber as the subject in the film. The cinematography technique contained in the film emphasizes realism where images are taken with a camera grip or handheld, or without using tools to make the movement of the camera more natural or like an eye view in a real situation. Real illusions make the subject feel close to the audience so that it successfully depicts non-verbal messages, depictions of messages through gimmicks, and the behavior of the subject (Mr. Iber). Several shots show the totality of Mr. Iber, such as taking care of customary forest documents and directly extinguishing forest fires.